2015
DOI: 10.1021/ed500658s
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Equilibrium Law Teaching Sequence for Secondary School Students To Learn Chemical Equilibrium

Abstract: A didactic sequence is proposed for the teaching of chemical\ud equilibrium law. In this approach, we have avoided the kinetic derivation and the thermodynamic justification of the equilibrium constant. The equilibrium constant\ud expression is established empirically by a trial-and-error approach. Additionally, students learn to use the criterion of comparison between equilibrium constant and reaction quotient to predict the direction of reaction. The teaching sequence takes into account the alternative conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We believe that the approach introduced by Ghirardi et al [7] might be a suitable starting point in this endeavor for change. However, a whole series of further research on this issue will still be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the approach introduced by Ghirardi et al [7] might be a suitable starting point in this endeavor for change. However, a whole series of further research on this issue will still be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Even macroscopic and microscopic understanding of the concepts by 7-10 years old children [5] was studied in the field of states of matter, particle composition of matter, phase changes and dissolving. The understanding of all three levels was studied by Hinton, Nakhleh [6] in the topic of chemical reaction, Ghirardi et al [7] in the topic of chemical equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…As the conducted analysis indicated, writing down the equation of chemical reaction occurring in the given system was not a problem for the students, however, as many as 1/3 of them forgot to mark the state of chemical equilibrium by appropriately written arrows. Difficulties encountered by students in distinguishing between complete and incomplete chemical transformations have already been reported in several works [4][5][6][7][8][9]. This proves a strong need for a wider explanation of equilibrium processes to pupils.…”
Section: IImentioning
confidence: 92%
“…Informal feedback from the students revealed that they valued having the virtual "chalk and talk" discussions. Through these discourses, the instructor was able to identify and clarify students' conceptual difficulties and misunderstandings 12 pertaining to topics such as chemical equilibria, which is considered to be one of the more complex concepts in chemistry. 13 Are You Paying Attention, and Do You Understand?…”
Section: ■ Introductionmentioning
confidence: 99%